2005
DOI: 10.1007/s10593-005-0212-6
|View full text |Cite
|
Sign up to set email alerts
|

Dioximes of 1,3-Diketones in the Trofimov Reaction: New 3-Substituted Pyrroles

Abstract: Dioximes of 1,3-diketones enter into the Trofimov reaction forming pyrroles containing an acyl or an O-vinyloxime substituent in position 3 of the pyrrole. In the case of sterically hindered dioximes the main reaction products are isoxazoles.Heterocyclic compounds containing a 3-acylpyrrole fragment are of interest for making new pharmacological preparations. For example, the cannabinoid activity of 1-alkyl-3-(naphthoyl)pyrroles [1] and 1-alkyl-3-(naphthoyl)indoles [2] is known, as is the antibiotic activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…52) in low yields. 171 The two pyrrole rings are non-planar and it was argued that the formation of the second pyrrolic ring from O-vinyloxime 227 was hindered due to the increased electron density at the 3-position of the existing pyrrolic ring compared with that at the 2-position. It was suggested that the bipyrrole formation occurs following a [3,3] sigmatropic rearrangement of an enehydroxylamine and that the electron-donating effect of the heterocycle on the O-vinyloxime 227 leads to a reduction of the C-H acidity of the neighbouring methyl group, which is unfavourable for tautomeric conversion of the vinyloxime into an enehydroxylamine.…”
Section: Cyclizations Involving Chiral Non-pyrrolic Reagentsmentioning
confidence: 99%
“…52) in low yields. 171 The two pyrrole rings are non-planar and it was argued that the formation of the second pyrrolic ring from O-vinyloxime 227 was hindered due to the increased electron density at the 3-position of the existing pyrrolic ring compared with that at the 2-position. It was suggested that the bipyrrole formation occurs following a [3,3] sigmatropic rearrangement of an enehydroxylamine and that the electron-donating effect of the heterocycle on the O-vinyloxime 227 leads to a reduction of the C-H acidity of the neighbouring methyl group, which is unfavourable for tautomeric conversion of the vinyloxime into an enehydroxylamine.…”
Section: Cyclizations Involving Chiral Non-pyrrolic Reagentsmentioning
confidence: 99%
“…Hinz et al have synthesized 2,2‘-bipyrrole using pyrolysis of 2-azido-5-(2-pyrrolyl)penta-2,4-dienoic esters. Apart from 2,2‘-bipyrrole, Zaitsev et al have also prepared 2,3‘-analogues of bipyrrole through the intermediacy of O -vinyloxime pyrroles. The first notable observation was made during the synthesis of CC-1065, a potent antitumor and antibiotic wherein 3,3‘-bipyrrole was the building block …”
mentioning
confidence: 99%